The one or the many? Narrating and evaluating Western secularization. Issue 1 (2nd January 2017) - Gregory, Brad S.
ABSTRACT: Secularization in the Western world is not a contrived combination of disconnected phenomena. It is a complex, long-term, multi-faceted process in which the central place of Christianity has greatly diminished in all areas of life since the sixteenth century, and which derives from the enduring doctrinal disagreements and recurrent religio-political conflicts of the Reformation era. Because late medieval Christianity was embedded in and intended to influence all areas of human life, including buying and selling, the exercise of power, and higher education, all areas of human life were powerfully affected by the Reformation's rejection of Roman Catholicism. By problematizing religion, the disagreements and conflicts inspired new ideas and institutional means to address them, and thus inadvertently contributed to secularization. The two principal accounts of long-term Western secularization – Enlightenment-liberationist and Catholic-disembedding – diverge not in their descriptions of what happened, but rather in their overall assessments of the process as respectively positive or not.